Psychosis in German prisoners: Comparison of the clinical appearance of psychotic disorder of an imprisoned population with a not detained community group. (24th August 2020) - Meinert, Philipp; Behr, Joachim; Gauger, Ulrich; Krebs, Julia; Konrad, Norbert; Opitz‐Welke, Annette
Abstract : Surveys confirm risk factors for the incarceration of patients with psychosis including homelessness and comorbidity. There is also agreement that severe psychosis can lead to violence. Data describing prisoners with psychosis in Germany are scarce. We aimed to compare patients with psychosis in a prison hospital and patients with psychosis in a community hospital. Demographic data were collected, as well as comorbidity in the form of substance dependence and a psychiatric assessment using the German version of the 18‐item Brief Psychiatric Rating Scale (BPRS) and the Positive and Negative Syndrome Scale (PANSS). In the prison hospital group more patients were homeless (17 versus 2%) and non‐German (36 versus 4%). There were also more patients with substance dependence or abuse in the prison hospital group. The total scores of BPRS and PANSS were lower in the prison hospital group (BPRS, 43.8 versus 51.2; PANSS, 71.5 versus 83.7). We assume that social disintegration for mentally disturbed offenders prior to incarceration hindered effective treatment. To avoid further social disintegration and possible further deterioration of mental health status of released offenders, which may lead to reoffending after imprisonment, discharge management after release from prison should be improved.